Thixotropic behavior of a waxy crude oil from the Malay Basin - Kaur, Jaspreet (2012)
Some complex materials, polymer solutions and waxy crude oils included, have been discovered to exhibit thixotropic behaviour. Thixotropy is a phenomenon where the viscosity decreases under constant shear rate followed by a gradual recovery over time when the shear rate is removed. All shear thinning fluids must show some degree of thixotropy due to the network structure disruption and spatial rearrangements, resulting in a decrease of viscosity, which do not occur instantaneously. Though in many cases, these changes are rapid and cannot be detected. In pipeline transportation of crude oil, for instance, it is important to characterize the thixotropic behavior of the crude oil in order for the flow characteristics to be well predicted and understood. Various methods have been proposed to quantify thixotropy, including the well-known “thixotropic-loop” tests. In this paper, the thixotropic behavior of a waxy crude oil from the Malay basin is explored together with the effects of temperature. Data showed that the extent of thixotropy increases with the reduction in temperature below the Wax Appearance Temperature of the crude oil. The regeneration of the crude oil structure also exhibited interesting features of the waxy crude oil.